Lactostasis and prevention of lactation mastitis: role of neonatologist and pediatrician - I. I. Ryumina; A. V. Levadnaya; V. V. Zubkov (Медицинский совет, 2020)
Breastfeeding is one of the main components of the health and optimal growth of a newborn child. The article presents recommendations on breastfeeding support in case of lactostasis and mastitis, as well as the role of neonatologist and pediatrician in prevention and preservation of breastfeeding when mother faces problems, lactation support in case of lactational mastitis development in mother. Prolonged lactostasis may be the cause of mastitis - breast inflammation, which is characterized by painfulness, swelling and redness of the breast. If the symptoms persist for 12-24 hours, in conditions of impaired milk evacuation the growth of microorganisms occurs, which leads to infectious lactation mastitis, which may be complicated by an abscess. The main risk factors of mastitis development, various methods of diagnostics, lactostasis and lactation mastitis prophylaxis are considered, and the special role of breastfeeding advice to the mother is emphasized. Data on modern and prospective method of lactostasis and mastitis prophylaxis - application of the product Lactanza based on Lactobacillus fermentum CECT5716 are presented. The use of probiotic bacteria was proposed as a method of modulating the immune system of a developing child to reduce the risk of immune aberrations and improve the immune protection of his or her body. According to the published data, there was a 51% reduction of mastitis frequency in the group that received probiotic Lactobacillus fermentum CECT5716. Therefore, it is advisable for women who start breastfeeding with increased risk factors for lactostasis and mastitis to recommend taking Lactobacillus fermentum CECT5716 probiotic immediately after childbirth during the first month of breastfeeding. The drug is also indicated for treatment of lactostasis in breastfeeding women to prevent mastitis from developing and after antibiotic therapy of mastitis to restore breast microbiome and lower the risk of relapse.